Utilization of psychotropic drugs prescribed to persons with and without HIV infection: a Danish nationwide population‐based cohort study. Issue 8 (3rd March 2014) - Rasmussen, LD; Obel, D; Kronborg, G; Larsen, CS; Pedersen, C; Gerstoft, J; Obel, N
<x xml:space="preserve">Abstract</x> Objectives The objective was to estimate the utilization of psychotropic drugs in HIV‐infected individuals compared with that in the background population. Methods Using data obtained from the Danish HIV Cohort Study and the Danish National Prescription Registry, we analysed aggregated data on redeemed prescription of psychotropic drugs during 1995–2009. We primarily focused our analyses on HIV‐infected individuals with no history of injecting drug use (IDU) or hepatitis C virus (HCV) infection. Drug utilization was expressed as defined daily doses per 1000 person‐days (DDD/1000PD). The utilization rate ratio (URR) was calculated as utilization in the HIV‐infected cohort compared with that in the comparison cohort. We estimated longitudinal trends in utilization and potential associations with HIV and exposure to highly active antiretroviral therapy (HAART), especially efavirenz. Results During 1995–2009, 54.5% of the HIV‐infected cohort (3615 non‐IDU/non‐HCV‐infected HIV‐infected individuals) and 29.2% of the comparison cohort (32 535 individuals) had at least one prescription of a psychotropic drug. HIV infection was associated with a URR of 1.13 for antipsychotics, 1.76 for anxiolytics, 4.42 for hypnotics and sedatives, and 2.28 for antidepressants. Antidepressants were confined primarily to men who have sex with men (MSM). Older age, more recent calendar time, and increased time after HIV diagnosis were associated with increased drug utilization. However, no association with exposure to HAART or efavirenz was found. Conclusions HIV‐infected individuals had a higher utilization of psychotropic drugs than the background population, which was not confined to individuals with a history of IDU or HCV infection. This emphasizes the need to focus on diagnosis of, and appropriate psychopharmacological interventions for, mental disorders in this population.